PELATIHAN BAHAN AJAR DAN INSTRUMEN NUMERASI BAGI GURU SD PLUS AL- GHIFARI BANDUNG - Nenden Mutiara Sari; Poppy Yaniawati; Eka Firmansyah; Euis Siti Aisyah; Siti Nurhayati; Mulyasari Yuningsih (LP2M Universitas Ibrahimy, 2023)
Teaching materials are an important requirement in realizing effective learning in schools. This problem requires the need for teaching materials as a solution to the problem of low numeracy skills. Some of the obstacles in learning mathematics are that teachers are less aware of the importance of preparing teaching materials according to their needs, the benefits of teaching materials in preparing learning tools and implementing learning, and teachers do not understand the mechanisms and techniques for preparing correct teaching materials. The preparation of teaching materials is very important, especially in improving students' mathematical abilities, especially numeracy. To provide solutions to these problems, the PKM Team conducted training on Teaching Materials and Numeracy Instruments for Elementary School Teachers. The stages that are passed are 1) preparation, 2) implementation and 3) evaluation. The participants of this training were 54 with the target audience of UNPAS Mathematics Education Master's students who teach in elementary schools and SD Plus Al-Ghifari mathematics teacher. The activity results showed an improvement in teachers' knowledge and skills regarding numeracy-based teaching materials and instruments, with an initial ability to obtain an average score of 27.04 and a final score with an average of 81.48. Meanwhile, participants' response to the PKM activity obtained a score of 4.6 in the highly satisfactory category. These activity results concluded that there was an improvement in teachers' knowledge and skills in developing numeracy-based teaching materials and instruments, and participants gave a highly satisfactory response to the training activity conducted.